Święty Jan Paweł II jako biskup krakowski : wybrane zagadnienia - Urban, Jacek (2020)
ST. JOHN PAUL II AS THE BISHOP OF KRAKOW: SELECTED ISSUES2020 marks the 100th anniversary of the birth of St. John Paul II. The author of the presented volume, referring to the aforementioned work, decided to publish a volume of several more texts. Its first part presents them in a chronological order. First, the sources of Karol Wojtyła’s spirituality are described, with particular reference to the Wawel Cathedral, where it grew in the last years preceding the outbreak of World War II and during its time. Then, Rev. prof. Karol Wojtyła’s ordination as bishop, his involvement in the Second Vatican Council and his ingress as the Archbishop of Kraków. The second group of texts deals with the topic of his relationship as the bishop of Kraków with several important milieus: (1) with the community of journalists of ‘Tygodnik Powszechny’ founded by Cardinal Adam S. Sapieha, against the bacground of communist reality, (2) to the environment of the Pontifical Faculty of Theology in Krakow and his concern for theology in the Church in Poland, to his close relations (3) with the Primate of Poland, Rev. Cardinal. Stefan Wyszyński, (4) to numerous religious congregations of the city of Krakow, or (5) to clerics forced by the authorities to perform military service, subjected to strong indoctrination in special military units. In the last part draws attention to the collections which preserve the legacy of Cardinal Karol Wojtyła. These are primarily the Archives of the Metropolitan Curia in Krakow, the Chapter Archive at Wawel and the Museum of the Archdiocese of Krakow located near Wawel in the place of residence of Bishop Wojtyła, from which, as a cardinal, he moved to the House of Archbishops of Krakow at Franciszkańska 3.The conclusion presents two important activities of Krakow bishops, the successors of Rev. Cardinal. Wojtyła. The first is the initiative of Rev. Cardinal. Stanisław Dziwisz to publish the critical edition of Karol Wojtyła’s literary works (the first volume has already appeared, the second will be published soon, the third is in preparation). The second is the initiative of Archbishop Marek Jędraszewski to publish the philosophical and theological works of Cardinal Karol Wojtyła. This year, the first volume of the inventory catalogue of the Wojtyła Archive will appear, and it will then be translated into English. This year, the first volumes of both series will be published. Within 5 years, some volumes of philosophical works and several volumes of theological works of Karol Wojtyła are scheduled to be published. Both initiatives are accompanied by the same notion to show and popularise the reflection and work of Cardinal Karol Wojtyła, as a prerequisite for becoming acquainted with the thought and work of the pontificate of St. John Paul II.